Avaliação Do Sleep Onset Rapid Eye Movement Period (Soremp) Noturno No Diagnóstico De Narcolepsia De Pacientes Com Sonolência Excessiva Diurna Do Ambulatório De Narcolepsia Da Universidade Federal De São Paulo / Escola Paulista De Medicina - Fernandes, Gustavo Bruniera Peres [UNIFESP] (2017)
Objectives: The primary objective was to evaluate the nocturnal sleep onset rapid eye movement period (nSOREMP) prevalence in narcoleptics type 1 (NT1) and type 2 (NT2) patients. The secondary objective was to evaluate the diagnostic sensitivity and specificity of non-invasive, clinics and electrophysiological, methods as predictors of cerebrospinal fluid Hypocretin-1 (CSF Hcrt-1) deficiency in a population of patients with narcolepsy diagnosis (by ICSD-3 criteria) attended at excessive daytime sleepiness outpatient clinic of Universidade Federal de São Paulo / Escola Paulista de Medicina in the period from 2011 to 2016. Methods: In a retrospective analysis of medical records, patients were distributed in tow groups, according the ICSD-3 criteria (NT1 and NT2), for nSOREMP prevalence estimation (ou rate). Subsequently the patients were divided into 5 groups to evaluate the association with CSF Hcrt-1 deficiency (Group 1 – CSF Hcrt-1 level; Group 2 – cataplexy presence; Group 3 – nSOREMP presence; Group 4 - HLA-DQB1*0602 presence; Group 5 – cataplexy plus HLADQB1*0602 presence). Results: A total of ninety-one patients were included, of which 34 (37.36%) were male, average age of 35,2 ± 14,6 years. The nocturnal SOREMP was more prevalent in NT1 patients (35%) than in NT2 patients (7.5%); p<0,001. Among the noninvasive methods studied, the presence of HLA-DQB1*0602 allele was the best predictor of Hcrt-1 deficiency. Conclusions: The nocturnal SOREMP was more prevalent in NT1 patients. As an alternative for predicting CSF Hcrt-1 deficiency, the presence of cataplexy associated with HLA-DQB1*0602 allele was the best noninvasive method studied. When considering the requirement for an invasive procedure to obtain CSF and technical and methodological difficulty to perform the CSF Hcrt-1 measure, these non-invasive and non-lab methods could be more assessed.